Effect Of Photoperiod Onto The Uptake Rate Of Phytoremediation Of Duckweeds - Zulkepli, Syafiqah (Universiti Sains Malaysia, 2021)
Macrophytes or aquatic plants are utilized by their nutrient removal abilities to reduce eutrophication and improve waste product quality. In this study, phytoremediation by L. minor and S. polyrhiza were carried out axenically in synthetic wastewater under control condition to precisely evaluate nutrient removal efficiency of NO3--N, PO43-, NH3-N and pH in the medium sample with different photoperiod. The results showed that ammonia removal was rapid, significant for Lemna sp. at photoperiod 8:16 h and S. polyrhiza at photoperiod 24:0 h with efficiency of 87.8% and 66.3% respectively within 3 days. L. minor was capable of reducing 14.7% of the nitrate. S. polyrhiza at photoperiod 16:8 h achieved phosphate reduction of 68.1% at day 3 to mere 7.17 mg/L PO4 3-. Both duckweeds showed biomass change increment. L. minor and S. polyrhiza at photoperiod 16:8 h outperformed other photoperiod in nutrient removal. By using the collected nutrient remediation profiles, it can be served as a guideline for the selection of suitable duckweeds and photoperiod in wastewater treatment and as microbiol activity assessment in non-aseptical phytoremediation system.